Environmental Research Communications - Environmental Research Communications (IOP Publishing, 2026)
Environmental Research Communications™  (ERC) is a high-quality, open access journal covering all branches of environmental research. ERC welcomes submissions from all domains of the Earth’s system, including atmosphere, biosphere, lithosphere, and hydrosphere as well as interdisciplinary studies between these. All environment-related research aimed at both disciplinary-specific and broad, multidisciplinary areas, and both global and regional, national, or even local studies (like case studies) are within the scope. All types of results can be published, provided they contribute to advancing knowledge in their field, including negative results, null results and replication studies. The journal does not make a subjective assessment on the potential future significance and impact of a paper, instead it provides a platform for rapidly communicating research that meets high standards of scientific validity and rigour and contributes to the development of our knowledge of the environment.
FI 0.51
Q3
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Acuerdos transformativos; Transformative agreements; Ciencias ambientales; Contaminación ambiental; Cambio climático; Calidad ambiental; Impacto ambiental; Sostenibilidad